2019
DOI: 10.1016/j.jaci.2018.12.1021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis for allergen immunotherapy

Abstract: The extensive use of allergen molecules in birth cohort studies revealed that atopic sensitization is a sequential IgE response to distinct non-cross-reacting molecules from the same allergenic source (ie, molecular spreading), starting with an initiator molecule. This phenomenon reaches different degrees of progression (monomolecular, oligomolecular, and polymolecular) according to the individual atopic propensity and allergen exposure, thus producing an extreme heterogeneity of IgE sensitization profiles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 101 publications
(144 reference statements)
5
60
1
1
Order By: Relevance
“…could not identify the majority of patients from southern Germany without sensitization to the 2 major allergens Der p 1 and/or Der p 2 and, therefore, is not suitable to close a diagnostic gap that arises when exclusively testing with components. On the other hand, specific knowledge of the exact sensitization profile is indispensable for the decision for allergen immunotherapy and its probable success [25,26]. Furthermore, Jiménez-Feijoo et al [10] reported that all elven HDM allergic patients of their collective who did not respond to immunotherapy were sensitized towards Der p 23.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…could not identify the majority of patients from southern Germany without sensitization to the 2 major allergens Der p 1 and/or Der p 2 and, therefore, is not suitable to close a diagnostic gap that arises when exclusively testing with components. On the other hand, specific knowledge of the exact sensitization profile is indispensable for the decision for allergen immunotherapy and its probable success [25,26]. Furthermore, Jiménez-Feijoo et al [10] reported that all elven HDM allergic patients of their collective who did not respond to immunotherapy were sensitized towards Der p 23.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…[310][311][312] These algorithms all incorporate the idea that detecting sensitization to genuine components is essential. 313 Although AIT for pollen-associated food allergy has shown beneficial effects in some studies, particularly for oral symptoms, other clinical trials have not shown similar outcomes; thus AIT cannot be recommended as a treatment in these cases and should be considered only when respiratory symptoms are present. [314][315][316][317][318] However, there are some fascinating potential applications in the field of immunotherapy: a research group in Vienna has recently generated mimotopes using a monoclonal antibody (BIP3) recognizing highmolecular-weight glycoproteins in birch and mugwort pollens, celery, and Apiaceae spices (anise, fennel, coriander, and cumin), which are responsible for the "celery-mugwort-birch-spice syndrome".…”
Section: Molecular Diagnosis and Allergen Immunotherapymentioning
confidence: 99%
“…Following adequate diagnosis algorithms, and a combination of in vivo and in vitro methods—which may include molecular allergology tools—are mandatory for deciding AIT intervention strategy in pediatric‐allergic patients . A comprehensive clinical guide for allergy diagnosis has already been published .…”
Section: Introductionmentioning
confidence: 99%